Pengembangan Media Pembelajaran Fisika Berbasis Web Enhanced Course dengan Model Inkuiri Terbimbing - Shabrina, Annisa; Diani, Rahma (Universitas Islam Negeri Raden Intan Lampung, 2019)
Abstract: This research aims; 1) knowing the feasibility of web-based physics learning media that is enhanced by courses with guided inquiry models in class X SMA measurement material; 2) knowing the students' response to the interest of web-based physics learning media that was enhanced by a guided inquiry model in the X grade high school measurement material. This study used research and development (R and D) method using Borg and Gall model. The data of this study were obtained from educator questionnaires and student responses, validation questionnaires for material experts, media experts, and informatics experts.The results of the study of material experts 87.45%, media experts 83.61%, informatics experts 77.29%, and educators in three schools 87.77%, while the responses of students in three schools 82.43%. Based on material experts, media experts, informatics experts, and educators, it can be concluded that physics learning media is a website as a learning medium.Abstrak: Penelitian ini bertujuan; 1) mengetahui kelayakan media pembelajaran fisika berbasis web enhanced course dengan model inkuiri terbimbing pada materi pengukuran SMA kelas X; 2) mengetahui respon peserta didik terhadap ketertarikan media pembelajaran fisika berbasis web enhanced course dengan model inkuiri terbimbing pada materi pengukuran SMA kelas X. Penelitian ini menggunakan metode penelitian dan pengembangan (R and D) dengan menggunakan modelBorg and Gall. Data penelitian ini diperoleh dari angket pendidik dan respon peserta didik,angket validasi ahli materi, ahli media, dan ahli informatika. Hasil penelitian ahli materi 87,45%, ahli media 83,61%, ahli informatika 77,29%, dan pendidik ditiga sekolah 87,77%, sedangkan respon peserta didik ditiga sekolah 82,43%. Berdasarkan penilaian ahli materi, ahli media, ahli informatika, dan pendidik, maka dapat disimpulkan media pembelajaran fisika berupa website layak digunakan sebagai media pembelajaran.